2021
DOI: 10.1111/petr.14049
|View full text |Cite
|
Sign up to set email alerts
|

Course of vitamin D levels before and after liver transplantation in pediatric patients

Abstract: VD plays an important role in health and many diseases notably by affecting the regulation of cell growth, inflammation, and the immune system. 1 VD stimulates innate immune cells such as macrophages to secrete anti-microbial peptides. 2 VD also controls adaptive immunity as the expression of >100 genes in T cells is altered by the interaction of VD and VD receptors in T cells. [3][4][5][6][7] For instance, VD increases IL-10 and FOXP3 expressing regulatory T cells, regulating both innate and adaptive immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…The vitamin D status in children with CLD usually improves after LT [ 19 ]. However, vitamin D deficiency can still be detected in post-LT children during long-term follow-up [ 8 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin D status in children with CLD usually improves after LT [ 19 ]. However, vitamin D deficiency can still be detected in post-LT children during long-term follow-up [ 8 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is common due to impaired 25-hydroxylation in advanced liver disease, limited exposure to UV light, and nutritional deficiencies. A study of 135 children who underwent liver transplantation showed a mean pretransplant vitamin D level of 14 ng/ml [11 ▪▪ ]. Prolonged vitamin D deficiency leads to secondary hyperparathyroidism, increased bone turnover and accelerated decline in bone mass.…”
Section: Pre-transplant Risk Factorsmentioning
confidence: 99%
“…Although the challenges in this vulnerable population remain unique, steroid withdrawal 48 and supplemental recombinant human growth hormone therapy 49 have been linked to positive outcomes in pediatric LT recipients, with a so-called "catch-up growth" phenomenon. Vitamin D supplementation is also recommended to correct the important insufficiency in children undergoing LT until levels are normal, 50 as fractures secondary to reduced bone mass and disorder of the bone architecture, particularly at the wrist, hip, and spine, can affect 20% to 40% of this population. 51…”
Section: Growth and Bone Developmentmentioning
confidence: 99%